Antioxidant, genotoxic and antigenotoxic activities of daphne gnidium leaf extracts - Chaabane, Fadwa (BioMed Central, 2012)
BACKGROUND: Plants play a significant role in maintaining human health and improving the quality of human life. They serve humans well as valuable components of food, as well as in cosmetics, dyes, and medicines. In fact, many plant extracts prepared from plants have been shown to exert biological activity in vitro and in vivo. The present study explored antioxidant and antigenotoxic effects of Daphne gnidium leaf extracts. METHODS: The genotoxic potential of petroleum ether, chloroform, ethyl acetate, methanol and total oligomer flavonoid (TOF) enriched extracts from leaves of Daphne gnidium, was assessed using Escherichia coli PQ37. Likewise, the antigenotoxicity of the same extracts was tested using the “SOS chromotest test”. Antioxidant activities were studied using non enzymatic and enzymatic method: NBT/Riboflavine and xantine oxidase. RESULTS: None of the different extracts produced a genotoxic effect, except TOF extract at the lowest tested dose. Our results showed that D. gnidium leaf extracts possess an antigenotoxic effect against the nitrofurantoin a mutagen of reference. Ethyl acetate and TOF extracts were the most effective in inhibiting xanthine oxidase activity. While, methanol extract was the most potent superoxide scavenger when tested with the NBT/Riboflavine assay. CONCLUSIONS: The present study has demonstrated that D. gnidium leaf extract possess antioxidant and antigenotoxic effects. These activities could be ascribed to compounds like polyphenols and flavonoid. Further studies are required to isolate the active molecules.